Interventions to increase hand hygiene compliance in a tertiary university hospital over a period of 5 years: An iterative process of information, training and feedback. Issue 5 (14th November 2018) - Hoffmann, Magdalena; Sendlhofer, Gerald; Pregartner, Gudrun; Gombotz, Veronika; Tax, Christa; Zierler, Renate; Brunner, Gernot
Abstract: Aims and objective: To explore whether an iterative process of information and training paired with a feedback system to observed healthcare professionals and the respective management improves hand hygiene (HH) compliance. Background: Healthcare‐associated infections are a major risk for patient safety, and adherence to the "My five moments" (M5M) for HH varies significantly within organisations as well as within healthcare professional groups. Identified barriers in a baseline survey revealed the need of more information, training, repetitive compliance measurements and feedback to all healthcare professionals. Design: A quality improvement project using the method of direct observation of healthcare professionals in nonsurgical and surgical wards. Methods: Between 2013 and 2017, 6, 009 healthcare professionals were informed and trained, and HH compliance measurements were performed by hygiene experts. Compliance measurement results were documented in an online tool to give an immediate feedback to observed healthcare professionals. Additionally, a report was forwarded to the management of the respective department to raise awareness. Compliance rates per year were descriptively summarised. The research and reporting methodology followed SQUIRE 2.0. Results: In total, 84 compliance measurements with 19, 295 "M5M for HH" were observed in 49 wards. Overall, mean HH compliance increased from 81.9 ± 5.2% in 2013 to 94.0 ± 3.6% in 2017. Physicians' HH compliance rate improved from 69.0 ± 16.6% to 89.3 ± 6.6%, that of nurses from 86.0 ± 6.9% to 96.4 ± 3.1%, and that of others from 60.5 ± 27.9% to 83.8 ± 20.2%. All M5M for HH (#1–#5) increased over the study period (#1: +16.9%; #2: +20.5%; #3: +7.6%; #4: +5.9%; #5: +12.7%). Conclusions: Results demonstrated that an iterative process of information, training, observation and feedback over a period of 5 years can be successful in increasing HH compliance. Positive trends were observed for HH compliance rates across all healthcare professional groups as well as for all M5M for HH.